FORMATION OF COGNITIVE INDEPENDENCE FUTURE TEACHER IN THE STUDY PROCESS FOREIGN LANGUAGE AS A CURRENT PROBLEM MODERN PEDAGOGICAL SCIENCE - I.Yu. Sinyagovska (Academy of Cognitive and Natural Sciences, 2022)
The article deals with some actual problems concerning the formation o f future teacher cognitive self-directed activities in the process of foreign language studies.